Predicted values of C-reactive protein in patients with low BMI and high BMI, according to the relative abundance of Alistipes shahii patients with SLE (R2 = 0.23; P value of the interaction = 0.03). - Lourdes Chero-Sandoval (22683418) (2025)
Blue line represents values for patients with low BMI (≤ 30 kg/m2) and the red line represents values for high BMI (≥30 kg/m2). The model was adjusted for age, sex, and adherence to Mediterranean diet.